GE_GERICHTE A/1955/2013 vom 3. März 2014 - GE Cour de justice (2014)
; IMPÔT ; DÉLAI ; OBSERVATION DU DÉLAI ; RÉCLAMATION DE DROIT PUBLIC ; DÉLAI DE RECOURS; RÉVISION(DÉCISION) | LIFD.132.al1; LPFisc.39.al1; LIFD.147.al1; LPFisc.55.al1